EVALUASI KEBIJAKAN PENGOPERASIAN BRT OLEH PEMERINTAH KOTA SEMARANG GUNA MENGATASI KEPADATAN LALU LINTAS (dalm upaya menuju “SemarangSetara”) - Katata Jullyan Angga Nugraha; Margareta Suryaningsih; Fathurrochman Fathurrochman (Journal of Public Policy and Management Review, 2016)
From the explanation of the Semarang City Government viewed the outflow of commuters entering the city is big enough, those who come in on the job and returned home after finishing their work, plus the Semarang city population which has now reached 1.5 million, will certainly lead to the density of traffic flow at the some point in city. Through these phenomena, Semarang city government issued a BRT operation policy that is intended to overcome these problems, the policy also aims as appropriate which of these explanations is an effort in the reduction of traffic congestion. BRT Operation Policy BRT has been running since Okober 2010. The evaluation is needed by this program to see monitoring the BRT operation program by using the policies evaluation criterias by Peter Rossi. They are Operating Program that includes design program and implementation program also Population Target. The obstacle course is seen from the planning, implementation, and monitoring. Data collection techniques used is through observation , interviews , documentation and literature study with the informant staff at the Department of Transportation , Communication , and Information Semarang The results showed that the Operations BRT performance in realizing Semarang Setara was good, it's just still some obstacles such as human resources, limited budgetary funds until the minimal community participation. There are some suggestions to overcome these obstacles that can be done such as opening a new corridor, skill training to improve the quality of human resource, increasing the number of human resources for maximum public services, proposed adding the amount of the budget in accordance with the needs required in Semarang city budget and make efforts to disseminate to the public until they realize that traffic congestion is a complex problem and affects many other sectors.